194k views
1 vote
Solve the following equation. Show all steps.

4(3y – 6) = – 3(8 – 4y)

User Dargaud
by
5.0k points

2 Answers

2 votes

Answer:

0=0

Explanation:

Step 1: Simplify both sides of the equation.

4(3y−6)=−3(8−4y)

(4)(3y)+(4)(−6)=(−3)(8)+(−3)(−4y)(Distribute)

12y+−24=−24+12y

12y−24=12y−24

Step 2: Subtract 12y from both sides.

12y−24−12y=12y−24−12y

−24=−24

Step 3: Add 24 to both sides.

−24+24=−24+24

User KoljaTM
by
5.8k points
4 votes

Answer:

All real numbers

Explanation:

So we have the equation:


4(3y-6)=-3(8-4y)

First, distribute the left side:


12y-24=-3(8-4y)

Now, distribute the right:


12y-24=-24+12y

Subtract 12y from both sides. Both sides cancel:


-24=-24

This statement is true.

In other words, our solution is all real numbers.

And we're done!

User Nicholas Zographos
by
4.7k points